Rol educativo de enfermería en la prevención del abandono y deserción del esquema de vacunación en niños menores de 2 años, Centro de Salud Engabao, Playas, Guayas. Mayo 2019- septiembre 2019 - Delgado Ortega, Alexis Patricio (2019)
This research project aims to organize educational activities of nursing against the prevention of abandonment or desertion of the vaccination scheme in children under 2 years of age in the commune Engabao, canton Playas, Provincia Del Guayas. In the research the methodology that will be applied are deductive methods – logical historical, qualitative-quantitative, field, documentary, bibliographic, descriptive, correlational using techniques such as survey, and instruments such as questionnaire, interview structured by collecting adequate and accurate, true and sufficient information on the problem. The population will consist of 100 mothers or caregivers of children under 2 years of age registered in the vaccination card of the health center as abandoned and with incomplete schemes from which 100% will be taken for research carried out in the commune. The conclusion was that factors such as low community education plus low education, not being treated well by health workers, not receiving home visits, and low incomes from caregivers influence high s abandonment and desertion of the vaccination schedule in children. To address this problem, it is planned to educate childminders through educational talks in order to raise awareness of the importance of the vaccination scheme, vaccine-preventable diseases and the benefits of respecting their culture and beliefs.